Role of 25-Hydroxyvitamin D3 and 1,25-Dihydroxyvitamin D3 in Chicken Embryo Osteogenesis, Adipogenesis, Myogenesis, and Vitamin D3 Metabolism - Chen, Chongxiao; White, Dima Lynn; Marshall, Brett; Kim, Woo Kyun (Frontiers in Physiology, 2021)
A study was conducted to understand the effects of 25-hydroxyvitamin D3 (25OHD) and 1,25-dihydroxyvitamin D3 (1,25OHD) administration on the expression of key genes related to osteogenesis, adipogenesis, myogenesis, and vitamin D3 metabolism in the chicken embryo. A total of 120 fertilized Cobb 500 eggs were used in the current study and were reared under standard incubation conditions. On embryonic day three (ED 3), PBS (C), PBS with 40ng 1,25OHD (1,25D-L), 200ng 1,25OHD (1,25D-H), 40ng 25OHD (25D-L), or 200ng 25OHD (25D-H) were injected into the dorsal vein of developing embryos. Whole embryos were harvested at 1, 3, and 6h post-injection for gene expression analyses (n=8). Gene expression for key osteogenesis markers (RUNX2, BMP2, COL1A2, BGLAP, SPP1, and ALP), adipogenesis markers (PPAR-γ, FASN, and FABP4), myogenesis markers (MYOG, MYOD1, and MYF5), and the enzyme responsible for vitamin D3 inactivation (CYP24A1) were measured using qRT-PCR. Data were normalized by the ΔΔCT method and analyzed using a one-way ANOVA. Results indicated that at 1h post-injection, no differences were found among treatments. At 3h, the early osteogenesis differentiation marker, ALP, was increased by 1,25D-H and 25D-H, and 25D-H also stimulated expression of adipogenesis markers (FAPB4 and FASN). In contrast, the expression of myogenesis markers (MYOD1 and MYF5) was suppressed by 25OHD or 1,25OHD treatments, respectively. At 6h, a late osteogenic differentiation marker, SPP1, was increased by 25D-H. MYOD1 and MYF5 were continuously suppressed by 25OHD treatments or 1,25D-H. The evidence of vitamin D3¬¬ metabolite retention was assessed by measuring CYP24A1 expression. At 1h, there were no differences in CYP24A1 expression. At 3h, all treatments up-regulated CYP24A1 expression relative to control (PBS) embryos. However, at 6h, only the 25D-H group retained higher CYP24A1 expression compared to the other treatments. In conclusion, the results suggested both 1,25OHD and 25OHD induced chicken embryo osteogenesis and adipogenesis, but inhibited myogenesis during early chicken embryo development. The higher dosage of 25OHD showed a possibility of a longer retention time in the embryos.